Effect of Human Adenoviruses on the Response of Chickens to Sheep Erythrocytes - Béládi, Ilona (1973)
Human adenovirus types 6, 8, and 12 were immunosuppressive in chickens. A single intravenous injection of adenoviruses markedly depressed the 19S hemolytic plaque-forming cell response in the spleen to the immunization with sheep red blood cells. Hemagglutinin production was also decreased in adenovirus type 6-infected chickens. Adenoviruses caused a transient immunosuppression in chickens which could be detected 2 to 3 days after the virus infection, and no depressive effect was found 16 to 20 days after virus injection. The possible mechanism of immunosuppression observed is discussed.